THE IMPLEMENTATION OF THE INQUIRY LEARNING MODEL TO IMPROVE GEOGRAPHY LEARNING OUTCOMES OF CLASS XI IPS 1 STUDENTS AT SMAN 7 BULUKUMBA - Zhiddiq, Sulaiman; Septiani, Andi; Maddatuang, Maddatuang; Yusuf, Muhammad; Mannan, Abdul (Universitas Negeri Makassar, 2025)
This study aims to determine 1) how the learning outcomes are after using Inquiry Learning, 2) the differences in learning outcomes of class XI IPS 1 using the Inquiry Learning model and conventional learning models, 3) the effectiveness of using models in the geography learning process of class XI IPS 1 at SMAN 7 Bulukumba. Data analysis uses descriptive and inferential analysis. The results of the study showed that the learning outcomes of class XI IPS1 1) after using the Inquiry Learning model obtained an average value of 85.35, 2) the differences in learning outcomes of class XI IPS1 using the Inquiry Learning and conventional learning models were 85.35 and 78.60 there was an increase of 6.75, and 3) the effectiveness of using the Inquiry Learning model was 100, so the level of effectiveness of the Inquiry Learning model in this study was included in the very effective category.